Bouveret's Syndrome: 64-Slice CT Diagnosis and Surgical Management—A Case Report. (21st November 2012) - Sharma, Dinesh; Sood, Rajan; Tomar, Ashwani; Jhobta, Anupam; Thakur, Shruti; Sood, R. G.
Abstract : Gastric outlet obstruction caused by duodenal impaction of a large gallstone migrated through a cholecystoduodenal fistula has been referred to as Bouveret's syndrome. We present a case of gallstone-induced duodenal obstruction in an elderly female patient, diagnosed on a 64-slice MDCT scanner. One-stage surgery, that is, stone removal and cholecystectomy, was performed resulting in relief of obstruction and complete cure. Clinical features, multidetector computed tomography (MDCT) findings, and surgical management are discussed.